1994
DOI: 10.1007/bf02053600
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal adenocarcinoma:

Abstract: We must provide the pathologist with a minimum of six examined lymph nodes per surgical specimen for an optimal Dukes B assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Specifically, an adequate nodal harvest is more common in right colon lesions, non-emergent surgery, and higher stage lesions [30,35,36]. We identified a modest association between previous cancer history and lower rate of adequate nodal harvest, a finding not reported previously.…”
Section: Discussionsupporting
confidence: 43%
“…Specifically, an adequate nodal harvest is more common in right colon lesions, non-emergent surgery, and higher stage lesions [30,35,36]. We identified a modest association between previous cancer history and lower rate of adequate nodal harvest, a finding not reported previously.…”
Section: Discussionsupporting
confidence: 43%
“…The probability increased to 99 percent if 10 lymph nodes were examined. The authors concluded that 6 lymph nodes provided an accurate assessment of the presence of nodal metastasis and an optimal Dukes' B classification [5]. Goldstein et al and Maurel et al showed that the probability of correctly classifying a colorectal tumor as node positive increased with the number of examined lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature not clearly indicates how many nodes should be examined to accurately predict lymph node status [68, 23, 24]. One study showed that a colon specimen usually contains about 50 lymph nodes and that more than 70% of the lymph nodes containing metastases are smaller than 5 mm [9].…”
Section: Discussionmentioning
confidence: 99%